Antipolo Sports Complex - Diesta, Leopoldo V. Jr. (Manila : National University, 2000)
When sports and recreational facilities were opened to the entire population, a demand for community of different type facilities throughout the country was created.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Design framework -- Chapter 5. Analysis -- Chapter 6. Conclusion and recommendation.
Includes bibliographical references.
Keywords: SPORTS FACILITIES; SPORTS AND RECREATIONAL COMPLEX